2018
DOI: 10.1007/s00249-018-1317-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drug amlodipine on the charged lipid bilayer cell membranes DMPS and DMPS + DMPC: a molecular dynamics simulation study

Abstract: In this work, the effects of the anti-hypertensive drug amlodipine in native and PEGylated forms on the malfunctioning of negatively charged lipid bilayer cell membranes constructed from DMPS or DMPS + DMPC were studied by molecular dynamics simulation. The obtained results indicate that amlodipine alone aggregates and as a result its diffusion into the membrane is retarded. In addition, due to their large size aggregates of the drug can damage the cell, rupturing the cell membrane. It is shown that PEGylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Also, pressure isotherm studies have shown that DMPS monolayers collapse at an APL of ~0.40 nm 2 [69]. Computational studies provided estimations of 47.6 nm 2 in the gel (30 • C) and 55.6 nm 2 in the fluid phase (60 • C) for pure bilayers or ~0.60 nm 2 for bilayers containing small molecules [70]. The respective studies also provided bilayer thickness estimates of 4.0-4.4 nm, or ~3.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Also, pressure isotherm studies have shown that DMPS monolayers collapse at an APL of ~0.40 nm 2 [69]. Computational studies provided estimations of 47.6 nm 2 in the gel (30 • C) and 55.6 nm 2 in the fluid phase (60 • C) for pure bilayers or ~0.60 nm 2 for bilayers containing small molecules [70]. The respective studies also provided bilayer thickness estimates of 4.0-4.4 nm, or ~3.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this will reduce the system generation time, for each simulation. In the following examples, some systems are studied to indicate how successfully they are built by using this package 7,9 . In performing these simulations the forcefield parameters for validation cases are obtained from Lipidbook 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Also MD simulation studies have been used to elucidate the behavior of drug and drug carriers 3,4 with the phospholipid membranes as well as the mechanism involved in interaction between cell membranes, proteins and enzymes 5,6 . Besides, by analysis of the experimental and simulations it has been suggested that the structure of PLCMs in both pure and mixed forms, 7 play a critical role penetration of the drug in to the membrane 8 . In other words, the diffusion of drug or drug carrier through the membrane could be studied and analyzed using free‐energy analysis or pooling force analysis, to deduce the efficiency of the drug‐delivery system 4,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present molecular dynamics studies 39 42 , the adsorption and release of DOX have been investigated for CNT, functionalized with FA and tryptophan (Trp) (a non-polar aromatic amino acid) 43 in both neutral and acidic pH.…”
Section: Introductionmentioning
confidence: 99%